HARMONISASI DALAM KERJA: Etika Antar Rekan di Pengadilan - Khosyi'atul Qomariyah; Reza Aditya Firmansyah; Haidar Hafidh Fadillah (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Workplace harmony is a crucial factor in creating a conducive and productive environment, especially in the judiciary, which demands high professionalism and integrity. This article explores workplace ethics among colleagues in the court as a fundamental basis for maintaining harmony and work effectiveness. Using a qualitative approach based on literature studies and interviews, this research finds that effective communication, mutual respect, and adherence to professional ethical codes significantly contribute to workplace harmony. The findings emphasize that implementing good work ethics can enhance efficiency, reduce conflicts, and strengthen trust and cooperation among colleagues in the judicial environment.